Crystal Structure of Archaeoglobus fulgidus CTP:Inositol-1-Phosphate Cytidylyltransferase, a Key Enzyme for Di-myo-Inositol-Phosphate Synthesis in (Hyper)Thermophiles - Brito, José A. (American Society for Microbiology, 2011)
Many Archaea and Bacteria isolated from hot, marine environments accumulate di-myo-inositol-phosphate (DIP), primarily in response to heat stress. The biosynthesis of this compatible solute involves the activation of inositol to CDP-inositol via the action of a recently discovered CTP:inositol-1-phosphate cytidylyltransferase (IPCT) activity. In most cases, IPCT is part of a bifunctional enzyme comprising two domains: a cytoplasmic domain with IPCT activity and a membrane domain catalyzing the synthesis of di-myo-inositol-1,3′-phosphate-1′-phosphate from CDP-inositol and l-myo-inositol phosphate. Herein, we describe the first X-ray structure of the IPCT domain of the bifunctional enzyme from the hyperthermophilic archaeon Archaeoglobus fulgidus DSMZ 7324. The structure of the enzyme in the apo form was solved to a 1.9-Å resolution. The enzyme exhibited apparent K(m) values of 0.9 and 0.6 mM for inositol-1-phosphate and CTP, respectively. The optimal temperature for catalysis was in the range 90 to 95°C, and the V(max) determined at 90°C was 62.9 μmol · min(−1) · mg of protein(−1). The structure of IPCT is composed of a central seven-stranded mixed β-sheet, of which six β-strands are parallel, surrounded by six α-helices, a fold reminiscent of the dinucleotide-binding Rossmann fold. The enzyme shares structural homology with other pyrophosphorylases showing the canonical motif G-X-G-T-(R/S)-X(4)-P-K. CTP, l-myo-inositol-1-phosphate, and CDP-inositol were docked into the catalytic site, which provided insights into the binding mode and high specificity of the enzyme for CTP. This work is an important step toward the final goal of understanding the full catalytic route for DIP synthesis in the native, bifunctional enzyme.